UJI MIKROBIOLOGIS BEBERAPA PRODUK SAOS CABAI KILOAN PRODUKSI LOKAL YANG BEREDAR DI BEBERAPA PASAR KOTA PADANG - Monica, Metatia; Fifendy, Mades; Nurmiati, Nurmiati (Pendidikan Biologi, 2013)
ABSTRACTChili sauce is a sauce derived from the main ingredient of chili peppers (Capsicum sp) of good quality, which is processed by adding spices with or without the addition of other foods and food additives that are allowed. Many outstanding chili sauce, ranging from truly hygienic until sauce that has a mixture of substances hazardous chemicals. This is due to the increasing number of home industry sprung up that are not wearing the correct rules to make the sauce. This study aims to determine the microbiological quality of the chili sauce outstanding local production in some of the market town of Padang. The method used in this study is a descriptive study. The sample in this study is 3 brand chili sauce and 1 sample comparison (brands that are well known and registered in FDA). Sampling was done with the survey directly to the 7 markets in the city of Padang. This study was conducted from July to August 2013 at the Faculty FMIPA Unand microbiology laboratory. The results showed there is microbial contamination in a local production of chili sauce Coliform bacteria and molds. Two samples were contaminated with Coliform bacteria characteristic of the presence of the turbid medium containing the sample and there is a gas bubble in the Durham tube, it indicates the presence of bacteria capable of fermenting carbohydrates (lactose). Fungi of the genus Aspergillus are found by 2 species, genus Penicillium by 2 species and 1 species which could not be identified (Unidentification). Could be concluded that the chili sauce kilogram outstanding local production in some of the market town of Padang identified contaminated by microbes.